2014
DOI: 10.1088/1752-7155/8/2/027110
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines and VEGF measured in exhaled breath condensate are correlated with tumor mass in non-small cell lung cancer

Abstract: Inflammation mediated by the immune system is known to be important in carcinogenesis and, specifically, T helper 17 cells have been reported to play a role in tumor progression by promoting neo-angiogenesis. The aim of this study was to investigate whether inflammatory cytokines and vascular endothelial growth factor (VEGF) levels in exhaled breath condensate (EBC) and in serum were related to tumor size in patients with non-small cell lung cancer (NSCLC). Il-6, IL-17, TNF-α and VEGF levels were measured in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…However, Brusino et al . [16] reported that serum IL-17 level was similar in lung cancer patients as in healthy volunteers, although its level was higher in exhaled breath condensate. In addition, Teng et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, Brusino et al . [16] reported that serum IL-17 level was similar in lung cancer patients as in healthy volunteers, although its level was higher in exhaled breath condensate. In addition, Teng et al .…”
Section: Discussionmentioning
confidence: 99%
“…EBC collection techniques exhibit several advantages, including non-invasiveness, simplicity in their execution and high repeatability (5,6). The detection of tumour markers in EBC may be a novel approach to diagnose lung cancer in the early stages and in screens of high-risk groups (7)(8)(9)(10). In the present study, cancer embryo antigen (CEA) and endothelin-1 (ET-1) were detected in the EBC of 133 patients with NSCLC.…”
Section: Introductionmentioning
confidence: 78%
“…Many studies have suggested that the mechanism by which IL-17 promotes angiogenesis or lymphangiogenesis is related to VEGF and its receptor family. Brussino et al [35] showed that IL-17 expression in exhaled breath condensate from patients with NSCLC was correlated with VEGF-A expression. Lin et al [36] confirmed that in lung cancer patients, serum IL-17 was positively correlated with VEGF-A expression.…”
Section: Il-17 Promotes Angiogenesis and Lymphangiogenesis Of Lungmentioning
confidence: 99%